MOTIVASI AUSTRALIA IKUT DALAM PEMBENTUKAN REGIONAL COMPREHENSIVE ECONOMIC PARTNERSHIP (RCEP) - Nurmala, Zikra; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aim to analyze the Australia’s Interest in the Regional Comprehensive Economic Partnership both political and economic interest on it. Regional Comprehensive Economic Partnership is a form of free trade agreement comprising 10 ASEAN countries and 6 ASEAN FTA partners.The data used in this study is a secondary data. Secondary data was obtained trough library research and search online media research. The writter used liberalism perspective and State level of analysis as a reference to analyze the interest of Australia in the Regional Comprehensive Economic Partnership. This study also uses the theory of National Interest related to the Australia interest.The result of this research is the Australia aim to improve the political economy of Australia trough integrating the cooperations between Australia and another Regional Comprehensive Economic Partnership countries that already exist to minimalize the barrier in order to achieve the National Interest of Australia and maximazing the opportunity.Keywords : Regional Comprehensive Economic Partnership, Australia Interest, Political Economy.